Hepatoprotektor Ekstrak Etanol Daun Kelor (Moringa oleifera) pada Ayam Petelur Fase Layer Akhir Produksi - Ridho Gusti, Tiara; Mushawwir, Andi; Latipudin, Diding (Jurnal Ilmu dan Industri Peternakan, 2024)
Twenty Hy-Line Brown laying hens aged 102 weeks were reared as research objects to determine the effect of an ethanol extract of Moringa oleifera leaves on the liver health of laying hens in the final layer of production. The study used a completely randomized design (CRD) with an experimental method consisting of 4 treatments and 5 replications. Each repetition consisted of one laying hen. The treatment was given for a maintenance period of 35 days, namely P0 = basal diet without ethanol extract of Moringa oleifera leaves; P1 = basal diet containing 0.08% ethanol extract of Moringa oleifera leaves; P2 = basal diet containing ethanol extract of Moringa oleifera leaves (0.12%); and P3 = basal diet containing 0.16% ethanol extract of Moringa oleifera leaves. Sampling was carried out by selecting one individual in each experimental unit, so that there were 20 samples. The parameters observed in the study were profiles of transferase enzymes (AST, ALT, and GGT) and profiles of free radical biomarkers (MDA, ALP, bilirubin, and uric acid). The results showed that administration of an ethanol extract of Moringa leaves in the ration had a significant effect (P 0.05) on the profile of the transferase enzyme and markers of free radical activity. The liver function of laying hens remained optimal after administering an ethanol extract of Moringa leaves with a content of 0.16% in diet.